The Role of Microfabrication and Nanotechnology in the Development of Microbial Fuel Cells. Issue 10 (23rd September 2015) - Rojas, Jhonathan Prieto; Hussain, Muhammad M.
Abstract Innovative solutions are paramount to the identification and development of alternative energy resources, specifically for the production of potable water. Microbial fuel cells (MFCs) are a trending emerging technology that promises green energy production while simultaneously treating wastewater. At present, several research efforts are working towards determining which bacteria, fuels, and materials are optimal for developing the most efficient MFCs; microsized MFCs have a key role in this goal. Therefore, in this Review, we summarize recent microfabrication techniques for building microsized cells and elaborate on their advantages and the challenges that need to be overcome. We will then focus on the integration of nanomaterials into MFCs and finish with an overview on the challenges to scale up MFCs and potential uses for these miniature cells.